PARAMILITARY FORCES OF INTERNATIONAL TERRORISM IS A GLOBAL PROBLEM OF INTERNATIONAL SECURITY - Ovcharenko, V. V.; Miroshnichenko, G. М. (Honor and Law, 2019)
The composition and structure of the paramilitary forces of international terrorism and disclosed methods of applying it when deploying armed confrontation. As members of the armed opposition appear paramilitary non-governmental organizations and international terrorist forces.